Who Should Bear the Burden of Covid-19 Related Fiscal Pressure? An Optimal Income Taxation Perspective - Mehmet Ayaz; Lea Fricke; Clemens Fuest; Dominik Sachs (Center for Economic Studies and ifo Institute (CESifo), 2021)
The COVID-19 pandemic has led to an increase in public debt in most countries. This will increase fiscal pressure in the future. We study how the shape of the optimal nonlinear income tax schedule is affected by this increase. We calibrate the workhorse optimal income tax model to five European countries: France, Germany, Italy, Spain and the UK. Applying an inverse-optimum approach to the pre COVID-19 economies we obtain the Pareto weights implicitly applied by the different countries. We then ask how the schedule of marginal and average tax rates should be optimally adjusted to the increase in fiscal pressure. For all countries, we find that the increase in fiscal pressure leads to a less progressive optimal tax schedule both in terms of marginal and average tax rates.
Keywords: H21; H23; 330; fiscal pressure; optimal taxation